Investigating Protein Structure and Evolution with SCOP2. Issue 1 (15th February 2018) - Andreeva, Antonina; Howorth, Dave; Chothia, Cyrus; Kulesha, Eugene; Murzin, Alexey G.
Abstract: SCOP2 is a successor to the Structural Classification of Proteins (SCOP) database that organizes proteins of known structure according to their structural and evolutionary relationships. It was designed to provide a more advanced framework for the classification of proteins. The SCOP2 classification is described in terms of a directed acyclic graph in which each node defines a relationship of particular type that is represented by a region of protein structure and sequence. The SCOP2 data are accessible via SCOP2‐Browser and SCOP2‐Graph. This protocol unit describes different ways to explore and investigate the SCOP2 evolutionary and structural groupings. © 2015 by John Wiley & Sons, Inc.